Study protocol of a clinical randomized controlled trial on the efficacy of an innovative Digital thErapy to proMote wEighT loss in patients with obesity by incReasing their Adherence to treatment: the DEMETRA study - Castelnuovo, Gianluca; Capodaglio, Paolo; De Amicis, Ramona; Gilardini, Luisa; Mambrini, Sara Paola; Pietrabissa, Giada; Cavaggioni, Luca; Piazzolla, Giuseppina; Galeone, Carlotta; Garavaglia, Giacomo; Bertoli, Simona, the DEMETRA Study Group; et al. (Frontiers in Digital Health, 2023)
Despite the increasing use of pharmacological and bariatric surgery to treat obesity, weight-loss lifestyle intervention remains the first-line treatment. Digital health is coming to meet individual needs and makes obesity treatment more accessible, so this work aims to evaluate the safety and performance of a Digital Therapy for Obesity App (DTxO) in improving weight loss and weight-loss maintenance in obese patients exposed to an experimental nonpharmacological treatment program. Here we present the study protocol of a prospective, multicenter, pragmatic, randomized, double-arm, placebo-controlled, parallel, single-blind study on obese patients who will be treated with a new digital therapy to obtain an improvement in their disease condition through the application of different simultaneous strategies (a dietary plan and customized advice program, a customized physical exercise program plan, a cognitive–behavioural assessment and program, alerts and reminders, dedicated section on prescribed drugs intake, and chat and online visits with clinical professionals). We believe that DTxO will offer a promising intervention channel and self-regulation tool holding the potential to reduce treatment burden and reach more people by replacing some in-person contact with phone or digital communication, improving self-engagement and reducing the high demands the “obesity pandemic” for both patients and national health services in terms of time, cost, and effort.